Infiltration OF 5Y-PSZ with thermally compatible glass: Strength, microstructure and failure mode analyses - Rodrigues, J. V.M. [UNESP]; Cruz, B. S. [UNESP]; Gomes, M. M. [UNESP]; Campos, T. M.B.; Melo, R. M. [UNESP] (Elsevier, 2023)
This study set out to develop a thermally compatible glass to be infiltrated into zirconia partially stabilized by yttrium oxide (5Y-PSZ), to characterize it, and to evaluate its structural reliability and mechanical behavior. 5Y-PSZ zirconia discs (N = 90), dimensions 1.5 mm × 15 mm were produced, polished with #600 alumina oxide and #1200 silicon carbide sandpaper in a polisher. Three groups of 5Y-PSZ discs were assigned (n = 30): Zctrl: as sintered zirconia, Zinf-comp: glass-infiltrated zirconia on the occlusal surface, and sintered, and Zinf-tens: glass-infiltrated zirconia on the cementing surface and sintered; for biaxial flexural strength testing (ISO 6872:2015). A gel was synthesized via the sol-gel method and applied to the ceramic surface. Mechanical assay data (MPa) were evaluated via Weibull analysis (α = 5%) and specimens via X-Ray Diffractometry (XRD), Scanning Electron Microscopy (SEM), and fractographic analysis. The Zinf-tens group showed a characteristic strength of 824 MPa and m = 9.9; Zinf-comp 613 MPa and m = 10.2; Zctrl 534 MPa and m = 8; all groups differed statistically (σ0). However, they were similar in structural homogeneity (m). XRD showed 20–50 μm of infiltration, which means dissolution of part of the yttrium and reduction in the size of the cubic grains. In addition, the Zinf-tens group presented a failure origin from inside the material. The developed glass infiltrated into zirconia partially stabilized by yttrium oxide, increasing its characteristic strength and structural homogeneity by reducing surface defects and changing the failure mode.
Keywords: Glass; Infiltration; Weibull; Zirconia